A study on factors of selecting smartphones of the Tabika Kemas teachers in Lahad Datu / Juliannie Sabdurani - Sabdurani, Juliannie (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2015)
Different people have different priorities when they select a smartphone, thus there is no "one size fits all" phone. Today there are too many smartphone models to enumerate, made by many different companies and running various operating systems. Choosing the right one can be a challenge, and despite the popularity. The order in which these factors matter to you will help narrow down your choices. If you insist on a hardware design that includes a physical keyboard, for example, that eliminates the iPhone and many other touch-only phones from consideration. If you're locked into Verizon or Sprint as your carrier, all GSM phones are out, and so forth. This study is about factors of selecting smartphones of the Tabika KEMAS teachers. It specifically studies in the area of Lahad Datu, Sabah. This study is based on data collected from a survey questionnaire and the data was analyzed to evaluate and determine the factors of selecting smartphones of the Tabika KEMAS teachers that influence the purchasing decision based on their age. The result of the study also suggested that respondents need to spend wisely and get information about smartphone in the market as is needed for them to be protect from any fraud. It is hope that the study can contribute to the improvement of the awareness of decision making in selecting the smartphones.